Phytochemical Analysis and Antifungal Activity of Phoebe excelsa Nees Leaf Extract - Anis Nurohma; Occa Roanisca; Ristika Oktavia Asriza (Stannum : Jurnal Sains dan Terapan Kimia, 2022)
Candidiasis is an infection caused by the fungus Candida albicans. Candidiasis was recorded in the second highest position as an infectious disease that accompanies HIV/AIDS, as many as 266 cases. Candidiasis is the highest infection caused by fungi and is opportunistic. Infections caused by candida albicans can generally be treated with antifungal medications. However, the use of drugs in the long term can cause resistance to these drugs, besides antifungal drugs can also cause various side effects. Therefore, in this study, an assessment of the phytochemicals of the ethanol extract of medang sang’s leaves and its bioactivity as antifungal Candida albicans will be carried out. Testing the content of secondary metabolites in medang’s leaves was carried out qualitatively by observing changes in the sample when reacted with reagents. Testing the antifungal activity of the ethanol extract of medang sang’s leaves was carried out in-vitro using the disc diffusion method. Results Based on the test, the ethanol extract of medang sang’s leaves contains alkaloids, flavonoids and tannins. The results of testing the antifungal activity of Candida albicans showed no inhibition, this was because the tang compound contained in the ethanol extract of medang sang’s leaves did not have antifungal activity against Candida albicans.